2019
DOI: 10.3389/fchem.2019.00398
|View full text |Cite
|
Sign up to set email alerts
|

Active Food Packaging Based on Biopolymers and Aroma Compounds: How to Design and Control the Release

Abstract: Aroma compounds are known to be efficient active agents for a broad range of applications (antimicrobial, anti-oxidant, insect repellent…) that are highly sought when aiming at extending shelf life of food or biological products. However, they are intrinsically odorant and volatile at ambient temperature, which restricts the processing routes used to introduce them in a polymeric matrix and can affect their mode of action and limit efficiency. Indeed, due to their high sensitivity toward temperature they can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…CDs have been used in food and pharmaceutical products for many years, largely to form inclusion complexes with problematic drugs to enhance their solubility [ 55 ]. In addition, previous studies have shown that CDs are useful as an antibacterial food packaging material when forming inclusion complexes with natural antimicrobial agents such as thymol and carvacrol [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. This embedment of an antibacterial agent into food packaging material is one strategy to inhibit bacterial growth.…”
Section: Application Of Cyclodextrinsmentioning
confidence: 99%
“…CDs have been used in food and pharmaceutical products for many years, largely to form inclusion complexes with problematic drugs to enhance their solubility [ 55 ]. In addition, previous studies have shown that CDs are useful as an antibacterial food packaging material when forming inclusion complexes with natural antimicrobial agents such as thymol and carvacrol [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. This embedment of an antibacterial agent into food packaging material is one strategy to inhibit bacterial growth.…”
Section: Application Of Cyclodextrinsmentioning
confidence: 99%
“…In relation to food packaging containing volatile compounds, the mechanism of action is based on the release of these compounds from the polymer matrix to the food sample to perform their technological function [ 4 ]. For this reason, the compatibility of the volatile compound with the polymer matrix and its capacity to be retained during processing are key parameters for the final validation of the active packaging for a specific food application.…”
Section: Retention Capacity and Controlled Release Of Volatile Commentioning
confidence: 99%
“…Volatile compounds such as aldehydes, terpenes, and sulfur compounds, among others, are efficient active agents for a broad range of food applications due to their intrinsic antimicrobial, antioxidant, insect repellent, and other properties that can be suitable to extend the shelf-life of food that degrade under different mechanisms. However, they are also odorant and volatile at ambient temperature, properties that difficult their successful incorporation into a polymer matrix leading to high losses of the volatile compound and the formation of degradation products after processing and drying of the new developed materials [ 4 ]. In order to solve this limitation, in recent years, different processing methods have been designed and implemented apart from the conventional ones such as extrusion or injection molding, the main processing techniques used in the packaging industry in which high temperatures are needed causing losses of volatile compounds near to 30 wt% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the selection of the proper antimicrobial, as well as the choice of its optimal loading, is an important and not an easy task in the design and application of antimicrobial packaging (Becerril et al, 2013;Wicochea-Rodríguez et al, 2019). Some of these substances can modify the organoleptic profile of the packaged foodstuff, or can be used only for a small variety of foods, or can affect the functional properties (i.e., gas permeability, tensile strength, transparency, thermal stability, etc.)…”
Section: Introductionmentioning
confidence: 99%